Asymmetric azomethine amines with azobenzene moieties – liquid crystalline and optical properties. Issue 10 (9th August 2019) - Iftime, Manuela-Maria; Cozan, Vasile; Airinei, Anton; Varganici, Cristian; Ailiesei, Gabriela; Timpu, Daniel; Sava, Ion
ABSTRACT: Three asymmetric azomethine-azobenzene intermediates (M1-M3), having internal reactive amine functional group, and both n -butoxy and p- chloro, p -methyl, o -methyl terminal moieties, have been synthesised by reacting asymmetric substituted azobenzene diamines with 4-butoxybenzaldehyde. Their proposed chemical structures were confirmed by FTIR and 2D-NMR spectroscopy. The mesomorphic behaviour was investigated by polarised optical microscopy (POM), differential scanning calorimetry (DSC) and room temperature powder X-ray diffraction techniques. Characteristic textures of smectic A and nematic phases have been observed for samples M1 and M2, while only unsolved texture was revealed for sample M3 at room temperature, showing sharp reflections in the medium-wide angle region. From X-ray diffraction measurements, a layered ordered structure of all compounds was established by analyzing successive scattering vectors ratios (qi / q1 ). The dependence of thermal behaviour on molecular parameters like: interdigitation parameter γ, dipole moment, molecular polarisability, halogen radius, was commented. The UV-Vis spectral investigations of the intermediates, performed in six solvents, revealed that the absorption bands were influenced by the substituent nature. Graphical Abstract: